2020
DOI: 10.1002/fsn3.1549
|View full text |Cite
|
Sign up to set email alerts
|

Intervention effect of Malus pumila leaf flavonoids on senna‐induced acute diarrhea in BALB/c mice

Abstract: The Malus pumila leaves are used as a kind of tea drink in China, and there are abundant flavonoids in the leaves of Malus pumila. In this study, BALB/c mice received senna extract solution via gavage, which induced acute diarrhea, and the interventive effect of Malus pumila leaf flavonoids (MPLF) was observed. The results showed that MPLF decreased the diarrhea index, and MPLF also decreased the capillary permeability in the abdominal cavity of mice. The result of serum cytokine detection indicated that MPLF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Rutin is also said to have antidiarrhoeal properties as it prevents entry of rotavirus and/or viral interactions with target cells in the gut [58]. Studies by Yi et al, [59] on senna induced diarrhoea in mice showed that presence of flavonoids like rutin, isoquercitrin, quercitrin, myricetin exhibit anti-diarrhoeal properties by controlling the abnormal increase in vascular permeability and alleviating the inflammatory response. Epicatechin has been shown to prevent cholera toxin induced diarrhoea [60].…”
Section: Discussionmentioning
confidence: 99%
“…Rutin is also said to have antidiarrhoeal properties as it prevents entry of rotavirus and/or viral interactions with target cells in the gut [58]. Studies by Yi et al, [59] on senna induced diarrhoea in mice showed that presence of flavonoids like rutin, isoquercitrin, quercitrin, myricetin exhibit anti-diarrhoeal properties by controlling the abnormal increase in vascular permeability and alleviating the inflammatory response. Epicatechin has been shown to prevent cholera toxin induced diarrhoea [60].…”
Section: Discussionmentioning
confidence: 99%
“…In senna extract-induced acute diarrhea in BALB/c mice, flavonoids from Malus pumila leaves lowered diarrhea index and decreased the levels of inflammatory cytokines like interleukin 6 (IL-6), interleukin 12 (IL-12), and tumor necrosis factor-α (TNF-α). This ameliorating effect was reported to be caused by ten flavonoids, namely rutin, hyperoside, isoquercitrin, taxifolin, quercitrin, hesperidin, myricetin, baicalin, neohesperidin dihydrochalcone and quercetin (Yi et al, 2020). Incidentally most of these flavonoids have been variously reported to be able to bind and inhibit various integral proteins of SARS-CoV-2 necessary for viral entry and replication in human cells (Alzaabi et al, 2021).…”
Section: Role Of Flavonoids Against Covid-19 Induced Diarrheamentioning
confidence: 99%
“…In a mice model of senna-induced diarrhea, the transdermal administration of Renzhu ointment has been shown to significantly reduce the frequency of loose stools, diarrhea rate and index, and fecal moisture content ( Zhong et al, 2023 ). Moreover, the BALB/c mice developed acute diarrhea via senna extract solution in accompany with a decreased expression of AQP3 in the jejunum, while interventions of Malus pumila leaf flavonoids at either 25 mg/kg or 50 mg/kg by gavage displayed antidiarrheal effects by increasing AQP3 expression ( Yi et al, 2020 ).…”
Section: Role and Regulation Of Aqp3 Expression In Diarrheamentioning
confidence: 99%